Optimalisasi Data Analitik Dengan Kecerdasan Bisnis Pada Perusahaan XYZ - Arief Rachman Hakim; Hadithya, Ryan (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2024)
The sophistication of technology has a major impact on company strategy. The rapid exchange of information results in a set of data. Data, if processed, will benefit the business. As a result, there is a need for data analysts to evaluate data sets in order to provide insight and assist firms in making business decisions. This study approach employs the VDM (Visual Data Mining) method, which is a process for comprehending and analysing a pattern or trend of abstract data presented visually. The findings of such an analysis generate a dashboard that can assist the organisation in measuring its business performance based on the data history that it has. Keywords: VDM, Data, Data Visualization